White Adipocyte Browning Effects of Sargaquinoic Acid in 3T3-L1 Preadipocytes (P06-109-19) - Lee, Sang Gil (Curr Dev Nutr, 2019)
OBJECTIVES: Brown and beige adipocytes are known to combat obesity and hyperlipidemia by increasing energy expenditure through non-shivering thermogenesis. Since sargassum serratifolium, a marine brown alga, exhibited anti-obesity effect through white adipose tissue browning in diet induced obese mice, the purpose of this study was to investigate the effects of sargaquinoic acid (SQA), a major component of S. serratifolium, on the induction of preadipocytes to beige adipocyte phenotype. METHODS: 3T3-L1 preadipocytes were treated with SQA which was isolated from S. serratifolium. Triglyceride (TG) accumulation in 3T3-L1 cells was determined by lipid staining (Oil Red O) and colorimetric TG quantification assay. Change of free glycerol level in cell culture medium and gene expression related to fatty acid oxidation by SQA treatment in the 3T3-L1 cells were also measured. In addition, the expression of mitochondrial DNA was examined using real-time PCR to determine the mitochondrial biogenesis during adipocyte browning. Brown adipocyte related gene expressions were analyzed using real-time PCR. Western blot assay was utilized to examine the AMP-activated protein kinase (AMPK) activity during white adipocyte browning. RESULTS: SQA induced the differentiation of white adipocytes to beige adipocytes suggested by an increase in multilocular lipid droplets, mitochondrial density, and the brown adipocyte-specific gene expressions including uncoupling protein 1 and PR domain containing 16. Also, SQA increased the lipolysis and fatty oxidation related gene expressions. SQA increased AMPK activity to induce the expression of brown adipocyte-specific genes, since AMPK inhibitor (dorsomorphin) decreased the brown adipocyte-specific gene expressions. CONCLUSIONS: These findings indicate that SQA induces white adipocyte browning by activating AMPK pathway, suggesting SQA has the potential to be used as a dietary supplement to treat obesity and related metabolic diseases. FUNDING SOURCES: This study was a part of the projects, “Development of functional food products with natural materials derived from marine resources” funded by the Ministry of Oceans and Fisheries, Republic of Korea.